2019
DOI: 10.3390/nu11092142
|View full text |Cite
|
Sign up to set email alerts
|

Child-Sensitive WASH Composite Score and the Nutritional Status in Cambodian Children

Abstract: Progress in health has occurred in the past decades in Cambodia, in terms of health service access and interventions, but several indicators, including the prevalence of malnourished children, remain alarming. The causes of undernutrition are often linked to inadequate access to water, sanitation and hygiene services but limited evidence exists on the direct association between poor WASH practices and children’s’ nutritional statuses. This study investigates the relationship between water, sanitation and hygie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 25 publications
1
24
1
Order By: Relevance
“…Parallelly, the increase in the stunting prevalence over time indicates that postnatal factors also contribute to the maintenance and development of stunting. Analyses conducted using the same data used for this study by other authors have identified several postnatal determinants of stunting in our study population, including inappropriate feeding practices, increased exposure to animal faeces leading to Giardia Duodenalis infection, high incidence of infections and inadequate water and sanitation practices [ 26 28 , 53 ]. Also, an interaction between wasting, infection and stunting in Cambodian under-five children has previously been documented [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallelly, the increase in the stunting prevalence over time indicates that postnatal factors also contribute to the maintenance and development of stunting. Analyses conducted using the same data used for this study by other authors have identified several postnatal determinants of stunting in our study population, including inappropriate feeding practices, increased exposure to animal faeces leading to Giardia Duodenalis infection, high incidence of infections and inadequate water and sanitation practices [ 26 28 , 53 ]. Also, an interaction between wasting, infection and stunting in Cambodian under-five children has previously been documented [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this is common in many community-based studies. Also, previous publications from the original analysis of these data addressed some of these aspects [ 27 , 28 , 53 , 69 ]. These papers have suggested that infections may be contributing to the occurrence of stunting [ 27 , 53 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infant and young child feeding practices were assessed per UNICEF and WHO indicators for appropriate breastfeeding (WHO, ), including early initiation of breastfeeding, breastfeeding status, duration of exclusive breastfeeding, and 24‐hr recall on breastfeeding and bottle frequency. The methodology of MyHealth longitudinal study presented in more details in our previous publications (Hondru et al, ; Manzoni et al, ; Som et al, ; Wieringa et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The present study used data collected under the Cambodian longitudinal study, "MyHealth," to quantify the impact of maternal MUAC on linear growth of infants during the first 3. (Hondru et al, 2019;Manzoni et al, 2019;Som et al, 2018;Wieringa et al, 2018).…”
Section: Data Sourcesmentioning
confidence: 99%
“…Improving water, sanitation, and hygiene, as well as housing and access to health services, will promote a healthy environment, will reduce the prevalence of infectious diseases and may affect the decreasing prevalence of malnutrition (UNICEF, 2015). (Manzoni et al, 2019;Kwani et al, 2019).…”
Section: Discussionmentioning
confidence: 99%